Far‐red photons have equivalent efficiency to traditional photosynthetic photons: Implications for redefining photosynthetically active radiation. (12th February 2020) - Zhen, Shuyang; Bugbee, Bruce
Abstract: Far‐red photons (701–750 nm) are abundant in sunlight but are considered inactive for photosynthesis and are thus excluded from the definition of photosynthetically active radiation (PAR; 400–700 nm). Several recent studies have shown that far‐red photons synergistically interact with shorter wavelength photons to increase leaf photochemical efficiency. The value of far‐red photons in canopy photosynthesis has not been studied. Here, we report the effects of far‐red photons on single leaf and canopy photosynthesis in 14 diverse crop species. Adding far‐red photons (up to 40%) to a background of shorter wavelength photons caused an increase in canopy photosynthesis equal to adding 400–700 nm photons. Far‐red alone minimally increased photosynthesis. This indicates that far‐red photons are equally efficient at driving canopy photosynthesis when acting synergistically with traditionally defined photosynthetic photons. Measurements made using LEDs with peak wavelength of 711, 723, or 746 nm showed that the magnitude of the effect was less at longer wavelengths. The consistent response among diverse species indicates that the mechanism is common in higher plants. These results suggest that far‐red photons (701–750 nm) should be included in the definition of PAR. Abstract : Canopy photosynthetic responses of 14 species indicate that far‐red photons (701–750 nm) are equally efficient at driving photosynthesis when acting synergistically with traditionally defined photosynthetic photons (400–700 nm).